Voice assistance in 2019. (January 2020) - Dale, Robert
Abstract: The end of the calendar year always seems like a good time to pause for breath and reflect on what's been happening over the last 12 months, and that's as true in the world of commercial NLP as it is in any other domain. In particular, 2019 has been a busy year for voice assistance, thanks to the focus placed on this area by all the major technology players. So, we take this opportunity to review a number of key themes that have defined recent developments in the commercialization of voice technology.